EDUKASI KESEHATAN REMAJA MELALUI KAMPANYE PENCEGAHAN MEROKOK, VAPE, MINUMAN KERAS, DAN PERGAULAN BERESIKO PADA SISWA SMA NEGERI 1 SAWA - Hasnawati Hasnawati; Muhammad Arba; La Ode Muhammad Fitrawan; Astrid Indalifiany; Loly Subhiaty Idrus; Asniar Pascayantri; Nurramadhani A. Sida; Dian Munasari Solo; Fadhliah Malik; Irvan Irvan; Ari Sartinah; Ocha Olyvia; Aisah Fitriani Aksan (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
Adolescence is a vulnerable period for risky behaviors such as smoking, vaping, alcohol consumption, and unsafe social relationships. Limited health literacy often causes adolescents to perceive these behaviors as normal. This community service program aimed to improve the knowledge and awareness of students at SMA Negeri 1 Sawa regarding the dangers of smoking, vaping, alcohol consumption, and the risks of unsafe social behavior and HIV/AIDS. The activity was conducted on January 2026, at SMA Negeri 1 Sawa, Konawe Utara Regency, involving 40 twelfth-grade students. The methods used included interactive counseling, discussion, question-and-answer sessions, educational games, and simple demonstrations. The results showed an increase in students’ understanding of the dangers of smoking and vaping, the negative effects of alcohol consumption, and the risks associated with unsafe social behavior. Students began to understand that vaping is not a safe alternative to smoking and that risky behaviors may affect their reproductive health and future. The high level of student participation during the discussion indicated that an interactive approach is effective for adolescent health education.